Teleconferencing with dynamic medical images. - Stahl, J.N (IEEE Transactions on information technology in biomedicine)
Dynamic images, a sequence of static images displayed in rapid succession and perceived as a continuous motion by the human eye, are widely used in medicine. One of the primary objectives of telemedicine is the transmission of such images to a distant location to manage clinical problems remotely. A broad variety of methods is available to acquire, store, transmit and display these images. However, the context of the clinical problem determines which of these methods can be deployed in a telemedicine solution. This paper discusses the advantages and disadvantages of the different technologies and presents an example of a teleconferencing system for interventional cardiology. This system acquires cardiac angiography and intravascular ultrasound images and transmits them over an existing Internet connection to a distant location. It is specifically optimized for clinical conferencing, where time is limited for each case presentation during the conference, compared to the relatively long time available for the conference preparation. The system takes advantage of this characteristic by transmitting the images well in advance of the clinical conference and displaying them synchronously at both locations during the conference. This allows for the preservation of the original image quality.